Evaluasi Penerapan Good Manufacturing Practices (GMP) pada UKM Dimsum XYZ di Kota Bandung - Euis Sridaryati; Dini Nur Hakiki (Food Scientia : Journal of Food Science and Technology, 2021)
The high interest in frozen food products during the pandemic caused many food industries with the scale of Micro, Small and Medium Enterprises (MSMEs) to start producing frozen food, such as dimsum. Dimsum itself is a medium risk product, so it needs to have an MD distribution permit. GMP is the basic requirement for granting an MD distribution permit certificate by BPOM. This study aims to evaluate the application of GMP (Good Manufacturing Practices) to SME Dim Sum XYZin Bandung. The study was conducted by interview and direct field observation.The results of the study show that the application of GMP in SME DimSum XYZ still doesnot meet the requirements of the GMP guidelines because there are still6 cases of minor deviations, 7 cases of major deviations and 9 cases of serious deviations. Serious deviations in the application of GMP in SME DimSum XYZ lie in factory sanitation, production equipment, product testing methods, supervision of the production process, and chemical storage.